Faktor Internal dalam Pengembangan Organisasi Sekolah Dasar: Studi di SD Negeri 19 Kampung Olo, Kota Padang - Rafif Al-Ghani (CV. ITTC INDONESIA, 2025)
This study aims to identify and analyze the internal factors that influence the organizational development of elementary schools, focusing on SD Negeri 19 Kampung Olo, Padang City. The research employs a qualitative descriptive approach with data collected through interviews, observation, and documentation. The study reveals that leadership style, teacher motivation, organizational culture, and internal communication are dominant internal factors shaping the school’s organizational development. Effective leadership fosters collaboration and innovation among teachers, while a positive organizational culture supports continuous improvement. The findings highlight the importance of strengthening internal dynamics to enhance school performance and adaptability in achieving educational goals.